JENIS DAN MOTIF PENGGUNAAN PERDUKUNAN DALAM OLAHRAGA BERDASARKAN PENGALAMAN MAHASISWA PRODI S1 ILMU KEOLAHRAGAAN UNESA - RIZKY YANTO, MOHAMMAD; PRAMONO, MADE (Jurnal Kesehatan Olahraga, 2019)
This qualitative descriptive study aims to determine the types and motives of shamanic use in sports. Researchers are interested in this phenomenon because shamanism in sports practice in society has been very mushrooming but there have been no scientific studies that raise this issue. The scope of this study is to focus on the experience of college students of Sport Science Study Program of State University of Surabaya. The speakers in this study were twenty college students with a variety of sports and home cities. The method of taking speakers is done by purposive sampling method. Data retrieval is obtained through interviews. Analysis of this study through three stages, namely data reduction, data presentation, and conclusion. The results of this study indicate that: first, the type of shamanic sport outlines based on its purpose divided into attacks (weakens the opponent), defend (self-protection), and support (increase ability). The type of media, treatment, and orders carried out by shamans and users vary greatly, but have characteristics that are very closely related to the purpose of shamanism in the sport. Second, the sociogenetic motive is the dominant motive in the results of this study. Cultural motives are the most influential motivating motives related to the use of shamanism in sports. Most of the practices of shamanism in sports that occur do not depart from the needs of the athlete, but rather like a derivative tradition in which the resource person plays as an athlete as well as a Javanese.Keywords: Sport, Shaman, Culture, Motive